Battered Woman Syndrome Questionnaire (BWSQ) Subscales: Development, Reliability, and Validity. Issue 7 (9th August 2019) - Millen, Danielle H.; Kennedy, Tom D.; Black, Ryan A.; Detullio, David; Walker, Lenore E.
ABSTRACT: The current study describes the development and evaluation of the reliability and validity of four components of a comprehensive assessment designed for the purpose of identifying women who manifest symptoms due to an intimate partner violence (IPV) relationship: The Battered Woman Syndrome Questionnaire (BWSQ). More specifically, the purpose of this study was to evaluate the factor structure, validity, temporal stability and internal consistency of four instruments for measuring current functioning of IPV survivors; (a) Interpersonal relationship (BWSQ-IR), (b) Sexual Dysfunction (BWSQ-SD), (c) Body Image (BWSQ-BI), and (d) Post-Traumatic Stress Checklist (BWSQ-PTSC). Overall, results indicate the BWSQ subscales have good temporal stability and internal consistency. Exploratory factor analysis of the four subscales indicate that each has a unidimensional factor structure. Internal consistency was high for each of the subscales. A two-way mixed effects model, intraclass correlation was used to demonstrate a high degree of test-retest reliability. Convergent and discriminant validity was demonstrated by comparing each subscale with the Revised Adult Attachment Scale (AAS), the Derogatis Interview of Sexual Functioning – Sexual Response (DISF-SR), the Objectified Body Consciousness Scale (OBCS) and the Trauma Symptom Inventory (TSI). The four instruments demonstrate sound psychometric properties as standalone measures as well as subscales of the BWSQ.